2019
DOI: 10.3791/59833
|View full text |Cite
|
Sign up to set email alerts
|

Transient Treatment of Human Pluripotent Stem Cells with DMSO to Promote Differentiation

Abstract: Despite the growing use of pluripotent stem cells (PSCs), challenges in efficiently differentiating embryonic and induced pluripotent stem cells (ESCs and iPSCs) across various lineages remain. Numerous differentiation protocols have been developed, yet variability across cell lines and low rates of differentiation impart challenges in successfully implementing these protocols. Described here is an easy and inexpensive means to enhance the differentiation capacity of PSCs. It has been previously shown that tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…A transient 24 hours DMSO treatment also does not affect cell toxicity as cell viability is comparable in untreated control and DMSO‐treated hPSCs prior to differentiation (Supporting Information Fig. S6D, S6E), consistent with prior reports .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…A transient 24 hours DMSO treatment also does not affect cell toxicity as cell viability is comparable in untreated control and DMSO‐treated hPSCs prior to differentiation (Supporting Information Fig. S6D, S6E), consistent with prior reports .…”
Section: Resultssupporting
confidence: 90%
“…In a prior study, we demonstrated that transiently treating hPSCs with dimethylsulfoxide (DMSO) for 24 hours prior to directed differentiation significantly increases the propensity for differentiation across all germ layers . This technique is now used by multiple laboratories to improve differentiation across species (including mouse, rabbit, primate, and human) into more than a dozen lineages, ranging from neurons and cortical spheroids to smooth muscle cells to hepatocytes . Although the DMSO treatment activates the retinoblastoma protein (Rb) and increases the percentage of hPSCs in the G1 phase of the cell cycle , it remains unknown whether the DMSO treatment simply enriches cells in G1 or whether there are intrinsic changes to the cell cycle following the DMSO treatment that may potentiate differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Group 5S + D showed a marked change in morphology of the HLC as compared to the other groups (Figure 4C). DMSO is well known to induce hepatogenesis in various types of stem cells, that is, ESC, 16 iPSC, 19,20 and MSC. 17 Expression of hepatocytes-specific protein markers are important for assessing the quality control of derivation strategies employed for differentiation to a terminal cell type using stem cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, DMSO is commonly used in the differentiation protocol of several cancer cell lines [ 30 , 31 , 33 ] and embryonic stem cell lines [ 8 , 13 , 16 18 ] in both mouse and human. In fact, recently several protocols have been established where DMSO pretreatment of human pluripotent cells is the key step to enhance efficiency of the differentiation protocol [ 19 , 34 ]. Yet, our analysis showed that exposure to much smaller amounts of DMSO for 48 hours did not affect pluripotency status or differentiation potential.…”
Section: Discussionmentioning
confidence: 99%